2006
DOI: 10.1212/01.wnl.0000244345.49809.36
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of LRRK2 mutations in early- and late-onset Parkinson disease

Abstract: The G2019S mutation is a risk factor in both early- and late-onset Parkinson disease and confirms the previous report of a greater frequency of the G2019S mutation in Jewish than in non-Jewish cases with Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
130
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 23 publications
7
130
0
2
Order By: Relevance
“…Although genetic determinants may be sexually dimorphic,21, 22 and a specific LRRK2 gender effect has been postulated,23 we confirm that the male predominance observed in Western populations with PD is not present in the G2019S mutation in LRRK2 PD 23, 24, 25. A higher relative proportion of LRRK2 carriers among women (45 vs. 55%) vs. men (40 vs. 60%) was observed 25, 26.…”
Section: Discussionsupporting
confidence: 72%
“…Although genetic determinants may be sexually dimorphic,21, 22 and a specific LRRK2 gender effect has been postulated,23 we confirm that the male predominance observed in Western populations with PD is not present in the G2019S mutation in LRRK2 PD 23, 24, 25. A higher relative proportion of LRRK2 carriers among women (45 vs. 55%) vs. men (40 vs. 60%) was observed 25, 26.…”
Section: Discussionsupporting
confidence: 72%
“…These pathogenic changes are clustered in 10 exons, mostly encoding the carboxyterminal region of the protein. By far the most frequent and best-studied mutation is c.6055G .A ( p.G2019S) that accounts for as many as 40% of cases of Arab descent (Lesage et al 2006), about 20% of Ashkenazi Jewish patients (Ozelius et al 2006), and 1% -7% of PD patients of European origin (Clark et al 2006;Zabetian et al 2006). Interestingly, three different founders have been described for the p.G2019S mutation and at least 29 patients have been reported to carry the mutation in the homozygous state (Klein and Lohmann-Hedrich 2007).…”
Section: Lrrk2 (Park8)mentioning
confidence: 99%
“…Identified genetic causes are responsible for only a small percentage of Parkinson's disease (PD) cases, and the lifetime penetrance of the most common causal mutation, LRRK2 G2019S, is estimated at approximately 30% [1][2][3][4]. Twin studies have found similar PD concordance rates in monozygotic and dizygotic twin pairs, suggesting a primary role for environmental etiologic determinants [5,6].…”
mentioning
confidence: 99%